Physio-biochemical and transcriptomic analysis of Bacillus amyloliquefaciens PG-4-induced salt stress tolerance in Macrotyloma uniflorum - Wu, Yanna; Guo, Changlin; Xiao, Yang; Li, Xinyong; Yu, Daogeng; Wan, Qi; Liu, Huizhuan; Zhang, Yindong; Zhang, Rui; Luo, Kai (Frontiers in Sustainable Food Systems, 2024)
Introduction Macrotyloma uniflorum is an important legume fodder crop and green fertilizer. Salinity impedes plant growth and productivity of legume crops by disrupting the ionic and osmotic balance and hormonal regulation. Plant growth-promoting rhizobacteria (PGPR) are rhizosphere bacteria that contribute to the improvement of plant growth through diverse physiological mechanisms. Methods In this study, the growth promoting characteristics of the isolated strain Bacillus amyloliquefaciens PG-4 were analyzed, and to further investigated the possible mechanism of PG-4 in mitigating the damage caused by salt stress in M. uniflorum plants through pot experiments. Results In presence of different salt levels, PG-4 showed a high potentiality to produce several plant growth promoting metabolites such as NH3, siderophore, 1-aminocyclopropane-1-carboxylic acid deaminase (ACC-deaminase), and hydrolytic enzymes. Inoculation of the PG-4 significantly enhanced plant tolerance to salt stress, as demonstrated by promotion of plant growth (shoot and root biomass) under salt stress condition. Furthermore, PG-4 improved salt tolerance of Macrotyloma uniflorum seedlings by affecting the antioxidant enzymes including peroxidase (POD) and superoxide dismutase (SOD), by increasing the levels of proline, soluble sugars and chlorophyll. Treatment with PG-4 increased the K+ content while decreased the Na+ concentration level under salt stress. Transcriptomic analysis revealed 5525 genes were differentially expressed (PG-4-inoculated versus non-inoculated samples) at 0 mM NaCl, of which 3277 were upregulated and 2248 downregulated, while 1298 genes were differentially expressed at 100 mM NaCl, of which 819 were upregulated and 479 were downregulated. GO and KEGG enrichment analyses showed that these DEGs were significantly enriched in several terms and pathways mainly involved in the regulation of the cellular redox state, cell wall modification, metabolic adjustments, hemoglobin, biosynthesis of secondary metabolites and plant hormone signal transduction. Discussion These data showed that Bacillus amyloliquefaciens PG-4 significantly enhance salt stress tolerance in Macrotyloma uniflorum plants during salt stress conditions. Therefore, the results may be useful for explaining the mechanism by which PGPR inoculation regulates the salt tolerance of crops.